Peningkatan Kemampuan Mengenal Bangun Ruang Melalui Video Animasi Untuk Siswa Tunagrahita Ringan Di SLB C YPPLB Makassar - Sitti Rahmah; Dwiyatmi Sulasminah; Usman Usman (JURNAL ORTO DIDAKTIKA, 2024)
The problem of this research is that students with mild mental retardation at SLB C YPPLB Makassar have not been able to recognize spatial shapes. The formulation of the research problem is